Effectiveness of the Cheerful Phonics Method to Improve the Ability to Recognize the Sounds of Bilabial Consonant Letter Symbols for Mild Mentally Impaired Children - Rahmanah, Firli; Kasiyati, Kasiyati (Jurnal Pendidikan Kebutuhan Khusus, 2023)
This research raises the problem of a child with mild intellectual disability in grade 5 at SLB Al-Ishlaah Padang who does not yet know the sound of consonant symbols. For this reason, the researcher wanted to see the effectiveness of the cheerful phonics method to improve the ability to recognize the sounds of the symbols of bilabial consonants for children with mild intellectual disability. The approach used is a quantitative approach with the type of experimental research in the form of single subject research and an A-B-A design. In phase (A1) the percentage of R's ability is 33.3% - 40.6%. In phase (B), the percentage of R's ability is 50% - 93.7%. In phase (A2), the percentage of R's ability is 89.6% - 93.7%. Judging from the data, there is a positive increase in R's ability. So this cheerful phonics method is effectively used to improve the ability to recognize the sound of bilabial consonant symbols for mild intellectual disability children.